The Efficacy and Safety of Fostamatinib in Elderly Patients with Immune Thrombocytopenia: A Single-Center, Real-World Case Series - Jessica Liu; Cyrus C. Hsia (Advances in Hematology, 2022)
Fostamatinib is a small molecule spleen tyrosine kinase (Syk) inhibitor that was approved for the treatment of adult patients with immune thrombocytopenia (ITP) in second-line therapy. Syk inhibition prevents cytoskeletal rearrangements during phagocytosis, allowing platelet survival in ITP. However, fostamatinib treatment in elderly patients with ITP has not been well established. We performed a retrospective review of all elderly patients (age greater than or equal to 65 years) who had started on fostamatinib for the treatment of ITP at a single tertiary care centre to evaluate its efficacy and safety. Seven patients, median age 80 years (range 78–94), four women and three men, all of Caucasian background, with various comorbidities, started fostamatinib 100 mg orally twice daily as second or subsequent line therapy. Patients had a diagnosis of ITP for a median of 6 years (range approximately 6 months–30 years), had six comorbidities (range 2–14), and experienced 2 unique prior lines of ITP therapy (range 1 to 6). Over 1290 days of fostamatinib exposure, two patients required dose escalation to 150 mg orally twice daily, while five patients remained on the initial starting dose of 100 mg twice daily. The median platelet count at the time of initiating fostamatinib was 25 × 109/L (range less than 10–193). The median time to response (defined as any first platelet count greater than or equal to 30 × 109/L) was 19 days (range 0–181 days), with two patients responding rapidly (5 days and 19 days). Two patients required dose escalation and rescue therapy, and these same two patients discontinued fostamatinib after 175 days and 216 days of treatment. Treatment was tolerated in all patients with no thromboembolic events observed. One death was noted and unrelated to treatment. Overall, fostamatinib was effective and safe for the majority of these very elderly patients with ITP.